The Influence of Task Skills, Organizational Culture, Internal Motivation, and Non-Physical Work Environment on Employee Performance - Maharani, Sinta; Lestari, Fatima Puji; Adzani, Amallya Nur; Akbar, Muhamad Asif Maulana (Proceedings Series on Social Sciences & Humanities, 2025)
The research was conducted on employees to determine whether task skills, organizational culture, internal motivation, and non-physical work environment affected employee performance both separately and simultaneously. A total sample of 30 respondents was gathered using questionnaire media and various data analysis techniques. These techniques included the classical assumption test, autocorrelation test, goodness of fit test, multiple line test, and goodness of fit test. Internal motivation has a positive and significant effect on worker performance, the non-physical work environment has a positive and significant impact on employee performance, and corporate culture has a significant negative impact on worker performance.